Stress-strain state of the kinematic chain «lumbar spine – sacrum – pelvis» in cases of asymmetry of articular gaps of the sacroiliac joint - Korzh, Mykola; Staude, Volodymyr; Kondratyev, Andrey; Karpinsky, Mykhaylo (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2015)
In the kinematic chain of the skeleton its important parts transmitting the load from the spine to the pelvis are the sacrum, the sacroiliac joints (SIJ) and ligaments surrounding them. SIJ dysfunction often leads to low back pain. Objective: To analyze the stress-strain state of SCJ with ventral, dorsal and interosseous sacroiliac ligaments at their normal condition and in cases of asymmetry of the joint space width. Methods: for the study the previously proposed virtual model synthesized and based on the lumbar spine, SIJ and pelvis CT scans of 20 patients and SIJ MRI scans of 10 patients was selected. Finite element model of the lumbosacral spine and SIJ were loaded from the upper vertebrae LI with vertical force of 400 N and 2000 N along the axis of the spine. Results: distribution of stress and strain in the SIJ and lumbosacral spine model obtained under conditions of asymmetry of joint spaces’ width indicates the changing in nature of functioning of the entire articulation. In the case of asymmetry of SIJ width asymmetry it was determined displacement of conventional axis of rotational mobility of the sacrum and significant redistribution of stresses and strains between the left and right joints and ligaments. While loading with 400 N for asymmetric joint space width it was determined an increasing of the value of tension in SIJ ligaments on the left and of the value of deformation on the right particularly in dorsal and interosseous sacroiliac ligaments. The values of tension in the sacrospinous, sacrotuberous and iliolumbar ligaments changed asymmetrically so as to maximally compensate violations caused by asymmetry of the joint space width. The same trends were found while loading with 2000 N but at the same time tensions in sacrospinous and sacrotuberous ligaments significantly increased indicating their important role in SIJ stabilization under conditions of increasing load. In the proposed SIJ with lumbar spine model mathematically substantiated an opportunity of nascence of functional deformation like «twisted pelvis».